Simultaneous Determination of Gimeracil, Oteracil, and Tegafur in Pure Blend and their Combined Capsules by Stability-indicating RP-UPLC Method - Kunala, Anusha (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: A trouble-free, simple, specific, and highly sensitive stability indicating phase UPLC method was developed for concurrent assessment of Gimeracil, Oteracil and Tegafur in pure and in their combined tablet formulation. Method: A separation was accomplished by using X-bridge BEH C18 (100 x 2.1 mm, 2.5 μm) column, mobile phase composition of ACN: Buffer (0.5M ammonium formate) (20:80 v/v) and isocratic elution at a flow rate of 0.2 mL/min and detection wavelength of 220nm. The extreme stress conditions like hydrolysis with acid and base, peroxide oxidation, thermal decomposition was used as per ICH specifications to assess the stability of the analytes in bulk and dosage forms. Results and Discussion: The retention times of Gimeracil, Oteracil and Tegafur were found at 1.610, 3.502 and 2.985 min. respectively. The proposed method has linear response in the concentration ranges from 14.5 to 87 μg/mL, 39.5 to 237 μg/mL and 50 to 300 μg/mL of Gimeracil, Oteracil and Tegafur respectively. The LOD and LOQ values were determined as 0.009 μg/mL and 0.026 μg/mL for Gimeracil, 0.23 μg/mL and 0.69 μg/mL for Oteracil and 0.93 μg/mL and 2.81 μg/mL for Tegafur respectively. The acceptance limits of Q2 of the ICH procedures were met by all method validation parameters. The stability of the approach may be seen in the fact that the degradation products from forced degradation tests were well-resolved from Gimeracil, Oteracil and Tegafur. Conclusion: The suggested RP-UPLC method was very sensitive, exact, stable indicator, and cost-effective. Because of this, the method has the potential for use in regular analysis in the quality control department as well as pharmaceutical manufacture of Gimeracil, Oteracil and Tegafur.